Presenting a Model of Self-sacrificial behaviors of Leaders in Organizations; Interpretive Structural Modeling (ISM) Method - Amir Hossein Abdallahzadeh; Seyyed Mohammad Moghimi; Hossein Imani (مدیریت دولتی)
Objective One of the most significant topics discussed in management and leadership literature is the concept of self-sacrifice. Due to its numerous positive implications, organizations need to develop leadership styles based on self-sacrificial behaviors. Despite various examples and instances of self-sacrifice exhibited by managers and leaders, research on self-sacrifice and its leadership implications has been neglected. Therefore, further research in this area can illuminate the dimensions and aspects of self-sacrificial behaviors in organizations. Methods This study employs the Interpretive Structural Modeling (ISM) method. It is an applied research project that utilizes interviews as the primary data collection method. Results The findings of the research indicate that the conceptual model of self-sacrificial behaviors in organizations consists of eleven components: "positive self-concept," "resilience," "social representation," "motivation to serve," "empathy and compassion," "awareness and knowledge," "goal orientation and idealism," "collective identity," "social learning and social contagion," "core values," and "crisis." According to the findings, the two dimensions of "awareness and knowledge" and "collective identity" are the foundational components of the model, as they influence all other components and have a two-way relationship with each other. This means that, in addition to being influencing factors for other components, they also impact each other. Additionally, based on the model, the components of "empathy and compassion" and "social learning and social contagion" are ranked next. These two components also have a mutual relationship with each other and are further influenced by the "crisis" component, which ranks below them. In fact, the critical condition, in addition to affecting the higher-level components, also impacts the lower-level components, indicating the significant influence of this variable in the model. The "motivation to serve" component is placed at the fifth level of the model. As shown by the direction of the arrows, this component is dependent on the three components of critical conditions, core values, and goal orientation and idealism. This means that the motivation to serve, as one of the antecedents of altruistic behavior, is influenced by the occurrence of critical conditions and the presence of core values, goals, and ideals of the individual. The remaining three components in the model—positive self-concept, resilience, and social representation—have the least influence and the most dependence on other components, indicating that they are more influenced by other components in the model. The "social representation" component is the most dependent in the model, meaning that a person's desire for social expressiveness is reliant on all other components except resilience, as resilience does not affect social expressiveness. Conclusion Based on the results of the study using ISM, two components are identified in the linkage region: "empathy and compassion" and "awareness and knowledge." These components are considered dynamic, meaning that any change in them can impact the entire system. The independent region includes five components: "goal orientation and idealism," "collective identity," "social learning and social contagion," "core values," and "crisis," indicating their strong influence and guiding role in the model. Additionally, the "social representation" component is placed in the dependence region, signifying its high reliance on other components.